Do critical and functional threshold powers equate in highly- trained athletes? - Mc Grath, E.; Mahony, N.; Fleming, N.; Raleigh, C.; Donne, B. (International Journal of Exercise Science, 2021)
The purpose of this investigation was to determine whether Critical Power (CP) and Functional Threshold Power (FTP) can be used interchangeably for a highly-trained group of cyclists and triathletes. CP was ascertained using multiple fixed load trials and FTP determined from a single cycling trial. Three different models for the determination of CP were initially addressed, one hyperbolic (Hmodel) and two linear (Jmodel and Imodel). The Jmodel was identified as most appropriate for a comparison with FTP. The Jmodel and FTP were not found to be interchangeable as ANOVA detected significant differences (282 ± 53 vs. 266 ± 55 W, p < 0.001) between these indices and the associated Bland-Altman 95% limits of agreement exceeded those set a priori. As the Jmodel was found to be consistently higher than FTP, a correction factor was posited to anticipate CP from FTP in this homogenous group of athletes using the mean bias (16 W). An alternate method for assessing CP trial intensities using Dmax as a proxy for ventilatory threshold is also proposed. The concept of both CP and FTP representing a maximal metabolic steady-state requires further investigation as the mechanical power at CP was significantly greater than at FTP.